Algerian’s Seismic Catalogue Completeness from Historical Instrumental Monitoring, Archeoseismological and Paleoseismological Studies. - Ayadi, A. (2022)
For any seismic hazard study, a reliable, homogenized and complete seismic catalogue is required. The Algerian seismicity catalogue has been recently updated by retrieving and reappraising many historical events. The Algerian seismic network has also been densified up to about 80 seismic stations covering the Tell Atlas which is the most active area of northern Algeria for monitoring of the seismic activity reducing the magnitude threshold. Recently, we have launched archeoseismological studies to retrieve past strong earthquakes that have affected Roman sites located along the Tell Atlas. Here, we proceed with tectonic investigations around selected sites where significant observed damage was identified. On the other hand, paleoseismological investigations were con- ducted along the El Asnam fault (now Chlef) following the large Ms 7.3 earthquake of 1980. Paleoseismic studies combined with archeoseismological results provide the dating of past earthquakes and contribute to the com- pleteness of the seismicity catalogue.